Identifikasi Sektor Basis dan Non Basis Berdasarkan Data PDRB Kabupaten Karo Menggunakan Metode Location Quotient (LQ) pada Badan Pusat Statistik Kabupaten Karo - Ade Putri Oktavia; Dwi Ananta Br Sembiring; Aishikin Jovanka; Fadillah Nay Marbintang Hrp; Hendra Cipta (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2026)
This study is motivated by the importance of identifying the economic structure and leading sectors of a region as a basis for regional economic development planning. Karo Regency, as one of the regions in North Sumatra Province, has economic potential that needs to be analyzed to determine sectors with comparative advantages. The purpose of this study is to identify base and non-base sectors in Karo Regency. The method used in this research is the Location Quotient (LQ) method with a descriptive quantitative approach. The data used are Gross Regional Domestic Product (GRDP) at constant prices by sector for the period 2021–2023 obtained from official publications of Badan Pusat Statistik Kabupaten Karo and Badan Pusat Statistik. The results show that the agriculture, forestry, and fisheries sector is a base sector with a comparative advantage in Karo Regency, indicated by an LQ value greater than one. Meanwhile, most other sectors are classified as non-base sectors with relatively smaller contributions compared to the provincial level. These findings indicate that the economic structure of Karo Regency is still dominated by the primary sector. The implication of this study is the need for development policies that focus on strengthening leading sectors while also promoting the development of non-base sectors to achieve a more balanced and sustainable economic structure.